INDONESIAN - ENGLISH CODE MIXING: A CASE STUDY OF BIPA LEARNERS. - ROFIAH, HASANATUR (LANGUAGE HORIZON, 2019)
ABSTRACT Rofiah, Hasanatur. 2019. Indonesian ? English Code Mixing: A Case Study of BIPA Learners. Language and Literature Department, State University of Surabaya. Advisor: Lina Purwaning Hartanti. Keywords: code mixing, BIPA, BIPA learners, social influence, personal reasons. For such a long time there is large number of studies that focuses on bilingualism and multilingualism issues likewise code mixing. However, most of the studies gave their focus on the phenomenon of language mixing between the first and the second language. Contrasting from the most frequent focuses, this study focuses on code mixing issues happened between the second and the third language on the certain chosen subjects. Thus, it affects to the findings which somehow quite different to what most commonly found in other previous studies with similar topic.This study focuses on code mixing occurred in BIPA learners? daily conversation. The research question proposed are: (1) what are the types of code mixing being used by BIPA learners of UNESA in the daily conversation, (2) what are the social factor that may influence the use of code mixing by BIPA UNESA learners, and (3) the reasons underlie behind the use of code mixing by BIPA learners. The main data were solely from the conversation between the researcher subjects and the subjects of this study which was recorded and transcribed. To collect the data, this study applied observation and interview which then analyzed and presented in a qualitative descriptive. The finding of this study shown that the most code mixing types occurred in BIPA learner?s utterances were insertion and alternation, yet the most dominant one was insertion. This study also disclosed that only several factors of code mixing influenced code mixing occurrence. Participant positioned as the first place of the main influencing social factor of code mixing, then followed by situation and act or topic of the talk. Code mixing between Indonesian and English was applied by BIPA learners because the very obvious main reason; the lack of Bahasa Indonesia comprehension. However, there also some other less dominant factors which appeared. Although they were studying Bahasa Indonesia the often mixed their utterances with English for they did not know certain terms in Bahasa Indonesia. However, prestige also turned out to be the next reason right after the main reason.